Molecular basis of oculocutaneous albinism type 1 in Lebanese patients - Zahed, Laila (2005)
Oculocutaneous albinism type 1 (OCA1) results from mutations in the tyrosinase gene, which lead to partial or complete loss of activity of the corresponding enzyme. A large number of mutations have been identified worldwide, providing insight into the pathogenesis of the disorder. We performed ophthalmic and dermatological exams on 30 Lebanese subjects with oculocutaneous albinism, then screened for mutations in the tyrosinase gene in an effort to establish the molecular basis of the disorder in our population and correlate it with phenotypic findings. The five exons of the gene together with the exon–intron boundaries and part of the promoter region were sequenced. Mutations were found in a total of 14 patients (47%) while no mutation was identified in the sequenced regions in 53% of patients. Fourteen different mutations were identified of which eight were novel while six had been previously reported. Mutations were mainly seen in patients with clinical findings, suggestive of OCA1A (64% of patients with OCA1A versus 25% of patients with OCA1B); therefore, the absence of mutations in some of the other patients may indicate the involvement of other genes.